Strategi Pemasaran Pada Produk Usaha Umkm Dalammeningkatkanprofit Penjualan Setelah Covid 19 : Studi Restoran Cv Citra Sari Kedele - Annisa Delia Septiani; Cindy Puspita Febrianti; Rosti Setiawati (STIE Bangkinang Publishing, 2023)
The title of this study is an analysis of marketing strategies to increase sales at theCvSari Soybean Restaurant business in Jatinangor District. This study aims to findout how the marketing strategy implemented by MSME businesses to increase sales. Thedataneeded by researchers uses qualitative data types and quantitative data. Thedatasources are primary data and secondary data. The methods used in collectingtherequired data: Interviews, and Literature Study. To find out how the strategy is usedSwotAnalysis Method (Strength, Weakness, Opportunity and Threat). Fromthe SWOTanalysisresults, it was found that the EFAS (External Factor Analysis Summary) resultsonthisMSME opportunity had good opportunities and the threat was quite high, judgingfromthemain product being sold, which is a product that is easy to imitate, this meansthatUMKM CV Citra Sari Soybean has the same opportunities and threats. The IFASvalueforthe variable strength of umkm Cv Citra Sari Kedele is very strong seen fromseveral aspects that are fulfilled and the weakness of this umkm is only the lack of promotiononsocial media. this shows that the strengths of these SMEs are greater than thevalueofthe weaknesses they have. From the results of the Swot analysis, it was foundthat theposition of MSME businesses has opportunities and strengths so that they cantakeadvantage of existing opportunities. The strategy that must be applied in this conditionisto support an aggressive growth policy.